Perlindungan hukum terhadap perempuan korban kekerasan berbasis gender: Analisis KDRT, kekerasan seksual, dan kekerasan seksual berbasis elektronik di Indonesia - Octariza, Sayyidah Belqis (Maliki Interdisciplinary Journal, 2026)
Gender-based violence against women remains a serious issue in Indonesia and manifests in various forms, including domestic violence, sexual violence, and electronic-based sexual violence (EBSV). The increasing number of violence cases against women indicates that existing legal protection mechanisms have not fully provided security and justice for victims. This study aims to analyze the forms of gender-based violence against women and examine the effectiveness of legal protection provided through various regulations in Indonesia. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through a literature review of laws and regulations, books, scholarly journals, and relevant documents. The findings reveal that Indonesia has established relatively comprehensive legal instruments through Law Number 23 of 2004 concerning the Elimination of Domestic Violence, Law Number 12 of 2022 concerning Sexual Violence Crimes, and various regulations governing electronic-based sexual violence. However, the implementation of legal protection still faces several challenges, including low public legal awareness, patriarchal culture, limited access to victim assistance services, and suboptimal law enforcement. Therefore, strengthening legal regulations, improving the capacity of law enforcement officers, and developing a victim-oriented protection system are essential to ensure the fulfillment of victims’ rights and recovery.